CASE STUDY: THE EFFECT OF CHITOSAN AND ZINC OXIDE OINTMENT FOR TREATMENT ON HEALING INCISION WOUNDS AFTER PERIANAL URETHROSTOMY SURGERY IN CATS AT THE DR.B SIDOARJO VETERINARY CLINIC - Balqis Ria Putri; Bilqisthi Ari Putra (Journal of Innovation Research and Knowledge, 2025)
Incised wound is tissue damage because it is sliced by a sharp and flat instrument such as a scalpel. Treatment of incision wounds is usually conventional, namely Povidone iodine 10% as an antiseptic can be irritating and inhibit granulation, while topical antibiotics can cause resistance if used inappropriately. Chitosan and Zinc oxide are therapies made from natural ingredients that can be used by minimizing side effects while accelerating tissue regeneration. Chitosan and zinc oxide have been shown to be effective in the use of burns in white rats and diabetic wounds in humans. This case study aims to see the effect of giving chitosan ointment and zinc oxide on the healing of incision wounds after perianal uretrostomy surgery in cats. This research method used domestic male cats with a BB of 4 kg who were treated with chitosan ointment and zinc oxide on the suture wound and observed until the 6th day after surgery. The wound healing parameters are seen from the degree of redness, swelling, inflammatory fluid, and the edge of the suture wound. The results showed that the degree of wound redness, swelling, inflammatory fluid, and wound edges occurred faster on the 1st and 3rd days postoperatively and the optimal effect of incision wound healing occurred in 6 days postoperatively without the presence of fibroblast tissue. The conclusion of this study is that chitosan and zinc oxide are able to provide a faster healing effect on cat incision wounds.